Effect of Coconut Milk and Benzyl Amino Purine on the Vegetative Growth, Nutritional and Chemical Constituent of Amaranthus Hybridus Linnaeus Seedlings (Global Journal of Science Frontier Research, 2014)
Studies were carried out to investigate the effects of 10%, 15% coconut milk and 50mg/L, 100mg/L Benzyl amino purine on the vegetative growth, nutritional and photochemical constituents of Amaranthus hybridus Linnaeus seedlings. Plants sprayed with water were the controls. All the treatments resulted in significantly increased leaf number, stem girth, plant height, shoot/root ratio, leaf area ratio and chlorophyll content of the vegetable with highest values recorded in treatments with 15% coconut milk at 14 weeks after planting. Treatments with 15% coconut milk also resulted in greater mineral elements contents at 14 weeks after planting of the vegetable. Alkaloids (3.55), saponins (1.66), phenols (0.36) and flavonoids levels (0.85) were higher in 15% coconut milk treated plants, whereas phytic acid (1.26) and hydrocyanic acids levels (15.30) were greater in 100mg/L Benzyl amino purine and 10% coconut milk respectively at 14 weeks after planting.
Keywords: amaranthus hybridus; coconut milk; benzyl amino purine; chlorophyll content; nutritional contents; phytochemical constituents